Closed Reduction Technique for Severely Displaced Radial Neck Fractures in Children. Issue 1 (4th January 2023) - Shah, Maulin; Gupta, Gaurav; Rabbi, Qaisur; Bohra, Vikas; Wang, Kemble; Makadia, Akash; Shah, Shalin; Sangole, Chinmay
Abstract : Background: The described technique is useful for achieving closed reduction of severely displaced (i.e., Judet Type-III and IV) pediatric radial neck fractures. It is widely agreed that radial neck fractures with angulation of >30° should be reduced. Various maneuvers have been described, but none uniformly achieves complete reduction in severely displaced radial neck fractures (Types III and IV) 1 -4 . The aim of the present technique is to achieve closed reduction in these severely displaced radial neck fractures without surgical instrumentation. Description: A stepwise approach is described. First, the radial head is viewed in profile under an image intensifier so that it appears rectangular. Varus stress is applied at the medial aspect of the elbow by the assistant, and thumb pressure is applied at the radial head along the posterolateral aspect of the elbow. This results in partial reduction of the radial head. The elbow is then simultaneously flexed and pronated with continuous pressure over the radial head. This final step anatomically reduces the radial head, and hyperpronating the forearm locks it in the corrected position. Alternatives: Operative alternatives to this technique include intra-focal pin-assisted reduction to achieve closed reduction, the Métaizeau technique of achieving indirect closed reduction of the fracture with the aid of a TENS (Titanium Elastic Nailing System) nail, and open reduction 5 . Nonoperative techniques have also been described for use with Judet Type-II and III fractures, but not with the severely displaced types described in the present article. Rationale: This technique takes into consideration the anatomy of the capsule and lateral collateral ligament complex. The biomechanical ligamentotaxis helps in achieving anatomic reduction of the radial head. Placing the forearm in pronation tightens the annular and lateral collateral ligaments and prevents redisplacement. There are potential complications with operative treatment, including the risk of nerve injury with percutaneous reduction techniques and the risks of osteonecrosis, premature epiphyseal fusion, and heterotopic ossification with open reduction. These complications can be avoided by the use of the presently described technique. Expected Outcomes: This technique provided satisfactory clinical outcomes in our previous study 6, with none of the 10 patients showing signs of growth disturbance, loss of reduction, or reported complications at 12 months. Terminal restriction of supination was observed in 1 patient. No patient had osteonecrosis or elbow deformity. No patient required conversion to an implant-assisted or open reduction procedure. Important Tips: The steps need to be followed sequentially as described in order to achieve an anatomical reduction. After achieving the reduction, it is necessary to keep the forearm in pronation to maintain the reduction with the aid of the lateral ligament complex. This technique may not work in complex fractures with elbow dislocation because of the lack of ligamentous integrity. In the final step, the elbow is pronated and flexed simultaneously, with sustained pressure over the radial head in order to obtain further correction. This is the most critical step of the technique because anatomic reduction of the partially reduced fracture is achieved at this time. Acronyms and Abbreviations: Percut. = percutaneous AP = anteroposterior CR = closed reduction ORIF = open reduction and internal fixation